Effects of holothuria extract on pain behaviour and Fos like immunoreactivity (FLI) in formalin pain - AA, Che Badariah; HA, Asma; H, Mohd Nizam; FA, Siti (IIUM Medical Journal Malaysia, 2011)
Introduction: The aim of this study was to determine the effects of gamat extract on pain behaviour and Fos like immunoreactivity (FLI) expression in the ventral posterolateral thalamus using the acute pain model. Materials & Methods: Fourteen Sprague-Dawley male rats (220-300 gram) were given intraplantar injection of 0.05ml formalin (1%) followed by intraperitoneal administration of either 4 mg/kg gamat extracts (Holothuria spp.) or saline (control). Behavioural changes were observed and rats were sacrificed 2 hours post-formalin injection. Immunohistochemistry testing was done on the brain sections. FLI was examined using a light microscope attached to an image analyser. The behaviour and FLI data were analysed using repeated measure analysis of variance and independent t-test respectively. Significance level was taken as p<0.05. Results: The control group has significantly higher pain scores compared to holothuria group (F (1) =13.635, p=0.003). There was significant reduction in the pain behaviour score in the holothuria group when compared to the control group in phase 1 (t (14) =2.9, p=0.012) and most of the time from 15 to 60 minutes post-formalin injection (t (12) =3.535, p=0.004). There was a significant reduction (P<0.05) in the number of FLI on the contralateral aspect of the ventral posterolateral thalamic nucleus in the group that received 4mg/kg of holothuria extract (63 3.18) compared to control group (84 6.36). Conclusion: This study showed that administration of holothuria extract significantly suppressed the pain behaviour and reduced the number of FLI in formalin injected rats compared to control.